2018
DOI: 10.3389/fimmu.2018.01847
|View full text |Cite|
|
Sign up to set email alerts
|

The Long Noncoding RNA MALAT1 Induces Tolerogenic Dendritic Cells and Regulatory T Cells via miR155/Dendritic Cell-Specific Intercellular Adhesion Molecule-3 Grabbing Nonintegrin/IL10 Axis

Abstract: By shaping T cell immunity, tolerogenic dendritic cells (tDCs) play critical roles in the induction of immune tolerance after transplantation. However, the role of long noncoding RNAs (lncRNAs) in the function and immune tolerance of dendritic cells (DCs) is largely unknown. Here, we found that the lncRNA MALAT1 is upregulated in the infiltrating cells of tolerized mice with cardiac allografts and activated DCs. Functionally, MALAT1 overexpression favored a switch in DCs toward a tolerant phenotype. Mechanisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 61 publications
6
57
0
Order By: Relevance
“…By contrast, the majority of Linc00402 and RP11-348F1.3 transcripts localized to the cytoplasm and this was unaffected by anti-CD3/CD28 stimulation ( Figure 3C ). These results are consistent with another T-cell lncRNA, Malat-1 ( 6, 11 ), and also in agreement with two independent in silico lnRNA subcellular localization prediction algorithms ( 10, 12 ).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…By contrast, the majority of Linc00402 and RP11-348F1.3 transcripts localized to the cytoplasm and this was unaffected by anti-CD3/CD28 stimulation ( Figure 3C ). These results are consistent with another T-cell lncRNA, Malat-1 ( 6, 11 ), and also in agreement with two independent in silico lnRNA subcellular localization prediction algorithms ( 10, 12 ).…”
Section: Resultssupporting
confidence: 89%
“…To our knowledge, the role lncRNAs play on allogeneic T-cell responses following HSCT was previously uncharacterized. However, several observations supported the hypothesis that lncRNAs influenced allogeneic T-cell function, including that lncRNAs are transcribed by T-cell subtype-specific transcription factors ( 5 ), they regulate T-cell functions critical for alloimmunity including cytokine expression and migration ( 5-7, 30, 31 ), they are associated with solid organ allograft rejection ( 32–34 ), they regulate Th1 effector responses in the setting of cardiac allograft rejection ( 33 ), and they favor murine tolerogenic dendritic cells following allogeneic cardiac transplantation ( 11 ). Here we showed that lncRNAs, such as Linc00402, are differentially expressed by allogeneic T-cells and regulate their function.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear paraspeckle assembly transcript 1 (NEAT1) is proven to use NACHT, LRR, and PYD domain-containing protein 3 (NLRP3) inflammasomes as molecular decoys for miR-3076-3p, so knockdown NEAT1 could facilitate the tolerogenic phenotype in DC, which prevents progression of experimental autoimmune myocarditis and induces immune tolerance in a heart transplantation model ( 70 ). The metastasis associated in lung adenocarcinoma transcript 1 (MALAT1) overexpression promotes DC-SIGN expression by functioning as an miR155-5p sponge in the DC cytoplasm, which derives DC to Tol-DC with low expression of costimulatory molecules and high IL-10 secretion, protecting mice from acute rejection after cardiac transplantation ( 71 ). Apart from these, some biological interventions have also been used to induce Tol-DC, such as mesenchymal stem cells (MSCs) ( 72 ), induced pluripotent stem cells (iPSCs) ( 73 ), and recombinant Schistosoma mansoni antigens ( 32 ).…”
Section: The Ex Vivo Induction Of Tol-dcmentioning
confidence: 99%
“…Dendritic cells are the most effective APCs, which are responsible for initiating the immune response of naive T cells, and participating in maintaining immune self tolerance, promoting T cells with regulatory function or inducing T cell anergy (29)(30)(31). In vivo transfer of Ag-loaded DC with a tolerogenic character is considered to be a promising treatment for Ag speci c negative regulation of immune response (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%